ANSIEDAD Y COMPORTAMIENTO DE LOS NIÑOS Y NIÑAS DE 7-8 AÑOS DE EDAD DE LA UNIDAD EDUCATIVA FE Y ALEGRÍA PERIODO ABRIL-AGOSTO 2019 - Orozco Guerrero, Orlando Roberto (2020)
This research aimed to determine anxiety and behavior within the classroom in children 7 and 8 years of age of the Educational Unit "FE Y ALEGRIA". This research took a quantitative approach, of non-experimental design, according to its level and Correlational scope, for the transversal time, of basic objectives and of field, the population was boys and girls of 7 and 8 years of age, with a sample of 104 children (65 boys and 39 girls). The instruments used for data collection were psychometric tests; for the independent variable was applied the psychological battery CAS test composed of 20 reagents in which the scales measure the levels of anxiety of children, while for the dependent variable the BASC test evaluation system of behavior in children and teenagers. Together we used different statistical programs for the analysis of data between them is SPSS which allows to identify the correlation between variables; where we could determine that if there is a significant correlation of bilateral ,018 between anxiety and behavior. Finally it was determined that the more anxiety the children present the behavior would change inside the classroom.